PENGARUH LEADER SUPPORT DAN CO WORKER COOPERATION TERHADAP JOB INSECURITY YANG DIMEDIASI OLEH OCCUPATIONAL SELF-EFFICACY PADA SUZUYA MALL KOTA BANDA ACEH - Maisarah Maisarah; Murkhana Murkhana (Departemen Manajemen, 2022)
This study aims to determine the relationship between Leader support and co worker cooperation on job insecurity with occupational self-efficacy as a mediator. The indicators discussed in the Leader Support variable are 8 indicators, the indicators discussed in co worker cooperation are 4 indicators, in the job insecurity variable there are 4 indicators, and in the occupational self-efficacy variable there are 5 indicators. Data was obtained through a survey of 121 people as a representative sample of the research population. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that leader support, co worker cooperation and occupational self-efficacy directly affect job insecurity. The results of the study also found that leader support had an effect on the mediator variable, namely occupational self-efficacy, so that occupational self-efficacy was able to become a mediator on the influence of the variable leader support and co worker cooperation on job insecurity.